La tutela della salute mentale per gli autori di reato con patologia mentale: diritto garantito o utopia? - Introduzione - Vari, Autori (Il sogno della farfalla, 2022)
This article introduces a monographic issue dedicated to the topic of mental health in Italian penitentiary institutes and in the services that replaced the old forensic hospitals (REMS). This issue gathers the professional experience of lawyers, psychiatrists, psychologists, nurses, and rehabilitation technicians in a series of contexts which considerably differ from psychiatric outpatient services. The aim of the introduction is to provide an overview of the mental pathologies prevalence in the jail population compared to the general. In addition, the article deals with the complexity of treating patient affected by a mental illness who have committed a crime. The clinical evaluation and the therapeutic intervention are often limited by the patient’s judicial conviction or by security measures.